Mechanisms coordinating peptidoglycan synthesis with the cell cycle in Staphylococcus aureus - Monteiro, João Miguel da Silva Queiroga (2018)
"The emergence and spread of antibiotic resistance in bacteria constitutes one of the major challenges to global public health and is predicted to further escalate during the 21st century. One of the most frequent multi-drug resistant pathogens is methicillin-resistant Staphylococcus aureus (MRSA), a gram-positive coccoid bacterium that causes difficult to treat infections with severe morbidity and mortality rates. Many of the commonly used antibiotics target steps in the biosynthesis of peptidoglycan (PG), a robust but flexible meshlike macromolecule that withstands the intense internal turgor in the cell, among other functions. The integrity of the PG layer is of the utmost importance to bacteria, which must ensure that incorporation of new PG strands and remodelling of the existing ones is timely coordinated with the progression of the cell cycle. Despite its clinical relevance, many fundamental biological processes in S. aureus remain to be elucidated.(...)".